Clinical implication of symptom for long-term outcomes after elective percutaneous coronary intervention. (25th November 2020) - Ryota, K; Wakabayasi, K; Shibata, K; Nishikura, T; Shinke, T; Tanno, K
Abstract: Background: The appropriate treatment for silent myocardial ischemia (SMI) is controversial. The prognosis of asymptomatic patients after percutaneous coronary intervention (PCI) is unknown. Asymptomatic patients might be sicker and have delay of diagnosis when they have coronary events in clinical course. We, thus, hypothesized SMI are associate with the poor outcomes after PCI for stable coronary artery disease (CAD). Purpose: The present study compared the long-term outcomes of patients with SMI vs. stable angina pectoris (SAP) after elective PCI. Methods: Our prospective registry database included 923 consecutive patients with CAD who underwent PCI from October 2015 to August 2018. Patients with emergent PCI, acute coronary syndrome at admission, or chronic total occlusion patients were not included. A total 613 patients (71.4±11.2 years, 75.7% male) who underwent elective PCI were studied. The end points included all-cause mortality, non-fatal myocardial infarction, and repeat revascularization. Results: They were divided into 2 groups according to symptom status: SMI (n=392) and SAP (n=221). SMI patients were predominantly men, and more frequently had diabetes mellitus (197 [50.4%] vs. 91 [41.2%], p=0.028), previous myocardial infarction (44 [11.3%] vs. 8 [3.6%], p=0.001) and heart failure hospitalization.Echocardiography showed SMI groups had reduced ejection fraction (56.9±12.6 vs 63.3±9.1, P<0.001), extended left ventricular internal dimension in diastole (48.5±6.2 vs 47.4±5.8, p=0.048) and left ventricular diameter at end systole (32.8±7.6 vs 30.5±7.5, p=0.001). Mean duration of follow-up was 20.9±10.6 months. The incidence of non-fatal myocardial infarction and repeat revascularization was similar between the 2 groups (10 [2.6%] vs. 5 [2.3%], p=0.82, and 50 [12.8%] vs. 30 [13.6%], p=0.77, respectively). The incidence of all-cause and cardiovascular mortality was more frequent in SMI patients (26 [6.6%] vs. 6 [2.7%], p=0.036, and 9 [3.1%] vs 1 [0.5%], p=0.035, respectively). Kaplan-Meier survival curves indicated that SMI patients had significantly higher all cause-mortality than SAP patients (log-rank, p=0.0184, Hazard ratio 1.24 (1.05–1.47), p=0.013). In multivariable analysis, SMI was an independent predictor of all cause-mortality (Hazard-ratio 5.17, 95% CI 1.35–34.29, p=0.014). Conclusion: In patients with stable CAD undergoing elective PCI, SMI was associated with an increase in mortality. Optimal care for SMI patients after PCI should be clarified in future studies. Funding Acknowledgement: Type of funding source: None